2018
DOI: 10.4103/jfmpc.jfmpc_115_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the frequency of polycystic ovary syndrome in women with and without epilepsy

Abstract: Introduction:Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders; the impact of epilepsy and antiepileptic drugs influences the function of hypothalamic–pituitary–gonadal axis and dysfunction of the endocrine system and reproductive hormones in women with epilepsy. This study was carried out with an aim of determining and comparing the frequency and intensity of the complications of the hirsutism in women with and without epilepsy in Tehran in 2016–2017.Materials and Methods:This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…That a certain connection may exist between epilepsy and PCOS was first proposed in 1984 (12). Recently, in a clinical study, WWE were more inclined (52.3%) to develop PCOS than women without epilepsy (18.3%) (10). In addition, a few other studies pertaining to reproductive endocrine disorders in patients with epilepsy have also confirmed that epilepsy could increase the hazards of reproductive endocrine disorders in WWE (16,38,39).…”
Section: Related Research Work On Epilepsy and Pcosmentioning
confidence: 91%
See 4 more Smart Citations
“…That a certain connection may exist between epilepsy and PCOS was first proposed in 1984 (12). Recently, in a clinical study, WWE were more inclined (52.3%) to develop PCOS than women without epilepsy (18.3%) (10). In addition, a few other studies pertaining to reproductive endocrine disorders in patients with epilepsy have also confirmed that epilepsy could increase the hazards of reproductive endocrine disorders in WWE (16,38,39).…”
Section: Related Research Work On Epilepsy and Pcosmentioning
confidence: 91%
“…PCOS is a prominent reproductive endocrine disorder in women of childbearing age (7,10,18), affecting 6%-10% (19,20), and is related to genetic factors, environmental factors, and some other causes, such as the use of ASMs, epilepsy, and obesity; it is thus a multifactorial disease (18,21,22). This syndrome can cause HA, PCO, ovulation disorders (ODs), elevated levels of luteinizing hormone (LH), and an imbalance in the ratio of luteinizing hormone to follicle stimulating hormone (LH/FSH); some patients also have metabolic changes such as IR/ hyperinsulinemia, obesity, and dyslipidemia.…”
Section: The Core Mechanism Of Pcos Is Related To the Abnormal Hpo Axismentioning
confidence: 99%
See 3 more Smart Citations